Investigation of thyroid blood tests and thyroid ultrasound findings of patients with rosacea. Issue 1 (13th December 2020) - Gönülal, Melis; Teker, Kenan; Öztürk, Aylin; Yaşar, Fatma Y.
Abstract: We aimed to investigate the relationship between rosacea and thyroid diseases by analyzing thyroid blood tests and ultrasound findings of our patients recently diagnosed with rosacea. This study was designed as a prospective, single‐center study. Dermatological examination findings, lesion locations were recorded, and rosacea clinical scores were calculated for all study group patients. The control group consisted of completely healthy women presented to our hospital during the study period for check‐up purposes. Serum‐free thyroxine, free triiodothyronine, thyroid‐stimulating hormone, antithyroglobulin antibody, antithyroid peroxidase antibody levels were measured, and thyroid ultrasound examinations were performed for all study participants. The entire study cohort consisted of 123 patients (63 cases and 60 controls). There was no significant difference between the groups in terms of mean patient age ( P < .05). Cheek was the most common lesion location (96.8%). There was no difference between the groups in terms of thyroid‐related laboratory parameters. However, anti‐TPO levels differed significantly with increasing disease severity (ie, RCSs). There were significant relationships between cheek lesions and fT4 ( P = .021), while nose and chin lesions were associated with fT3 ( P = .01, P = .001). Thyroid ultrasound findings revealed that rosacea patients tended to have larger thyroid nodules and more heterogeneous thyroid parenchymas than controls. Our findings indicate that thyroid blood tests, including thyroid autoantibodies, should be tested and thyroid ultrasounds should be performed in patients diagnosed with rosacea. However, these findings need to be validated by prospective studies conducted in larger patient series with more extended follow‐up periods.